2019
DOI: 10.1002/chem.201903058
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Reactions of Haloperfluorocarbons with Gold(I) Organometallic Complexes: Perfluoroalkyl Gold(I) and Gold(III) Complexes

Abstract: The study of perfluoroalkyl metal complexesi sk ey to understand and improvem etal-promoted perfluoroalkylation reactions. Herein, we report the synthesis of the first gold complexes with primaryo rs econdary perfluoroalkyl ligands by photoinitiated reactions between Au I organometallic complexes and iodoperfluoroalkanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 137 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…Oxidation with I 2 gave the Au(III) trans-diiodide which was stable only at very low temperatures and underwent thermal reductive elimination of CF 3 I. In the case of the other halides, trans-dihalide Au(III) trifluoromethyl complexes 157 are thermally stable but reductively eliminate CF 3 Br and CF 3 Cl when exposed to UV light (Scheme 52).Photoinitiated reductive elimination from perfluoroalkyl Au(III) complexes was investigated by Portuguès et al323 In line with the previous results on trifluoromethyl derivatives, perfluoroalkyl iodides were found to oxidatively add to LAuR complexes (L = PPh 3 , IPr; R = Me, Mes, alkynyl) under irradiation at 402 nm and afforded Au(III) complexes with variable stability. In the case of L Irradiation in the presence of radical traps revealed that the decomposition follows a radical mechanism, in analogy to what was proposed for the photoinitiatied oxidative addition (see Section 3.1.3).…”
mentioning
confidence: 99%
“…Oxidation with I 2 gave the Au(III) trans-diiodide which was stable only at very low temperatures and underwent thermal reductive elimination of CF 3 I. In the case of the other halides, trans-dihalide Au(III) trifluoromethyl complexes 157 are thermally stable but reductively eliminate CF 3 Br and CF 3 Cl when exposed to UV light (Scheme 52).Photoinitiated reductive elimination from perfluoroalkyl Au(III) complexes was investigated by Portuguès et al323 In line with the previous results on trifluoromethyl derivatives, perfluoroalkyl iodides were found to oxidatively add to LAuR complexes (L = PPh 3 , IPr; R = Me, Mes, alkynyl) under irradiation at 402 nm and afforded Au(III) complexes with variable stability. In the case of L Irradiation in the presence of radical traps revealed that the decomposition follows a radical mechanism, in analogy to what was proposed for the photoinitiatied oxidative addition (see Section 3.1.3).…”
mentioning
confidence: 99%
“…In contrast, complexes containing longer perfluoroalkyl chains have been much less explored. [9][10][11][12][13][14][15][16][17][18] Particularly, complexes containing difunctional perfluoroalkyl chains ( Figure 1) have received very little attention. Thus, a few binuclear complexes with bridging (CF 2 ) 2 chains have been prepared by insertion of C 2 F 4 into metal-metal bonds (A) [19][20][21][22] or by reaction of C 2 F 4 with low-oxidation-state metal complexes (B, C).…”
mentioning
confidence: 99%
“…The sluggish reactions observed in the dark or in the presence of TEMPO (Supporting Information) suggest a pho-toinitiated radical mechanism analogous to that proposed for the reactions of LAuMe with IC n F 2n+1 . [18] It is noteworthy that, whereas the Au I complexes LAu( n C 4 F 9 ) (L = PPh 3 or IPr) are unreactive toward I n C 4 F 9 , [18] complexes LAu(CF 2 ) n I undergo intramolecular oxidative addition when n is 4, but not when n is 6 or 8. Since the reaction of 2 equivalents of Me 3 PAuMe with I(CF 2 ) 4 I gave a complex mixture where the expected binuclear complex 1 h was a minor component, we synthesized it by a phosphine substitution reaction on 1 a (Scheme 1).…”
mentioning
confidence: 99%
“…The sluggish reactions observed in the dark or in the presence of TEMPO (Supporting Information) suggest a photoinitiated radical mechanism analogous to that proposed for the reactions of LAuMe with IC n F 2 n +1 . It is noteworthy that, whereas the Au I complexes LAu( n C 4 F 9 ) (L=PPh 3 or IPr) are unreactive toward I n C 4 F 9 , complexes LAu(CF 2 ) n I undergo intramolecular oxidative addition when n is 4, but not when n is 6 or 8. Since the reaction of 2 equivalents of Me 3 PAuMe with I(CF 2 ) 4 I gave a complex mixture where the expected binuclear complex 1 h was a minor component, we synthesized it by a phosphine substitution reaction on 1 a (Scheme ).…”
Section: Figurementioning
confidence: 64%
“…Notable progress toward this target has been made for metal trifluoromethyl complexes. In contrast, complexes containing longer perfluoroalkyl chains have been much less explored …”
Section: Figurementioning
confidence: 99%